2017
DOI: 10.22175/mmb2017.06.0033
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evaluation of Enhanced Beef Strip Loin Steaks Cooked to 3 Degrees of Doneness

Abstract: The objective of this study was to evaluate the impact of marbling level in combination with enhancement on beef palatability when strip loin steaks were cooked to 3 degrees of doneness. Consumer and trained sensory panelists evaluated strip steak palatability traits of 3 USDA quality grades: Prime, Low Choice, and Low Select. Additional strip loins from each grade were enhanced to 108% with a water, salt, and alkaline phosphate solution. Steaks from each treatment were cooked to 3 degrees of doneness (DOD; Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…Several studies have shown 51% to 76% of consumers prefer steaks cooked to a medium or higher DOD (Cox et al, 1997;Schmidt et al, 2002;McKillip et al, 2017b) and therefore further examination of this theory could benefit the industry by identifying products that will meet consumer eating expectations based on their preferred degree of doneness. Thus, the objectives of this study were to evaluate the extent marbling and enhancement compensate for reduced beef palatability at elevated degrees of doneness and to determine the relationship of residual moisture and fat in cooked steaks to beef palatability, specifically beef juiciness.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown 51% to 76% of consumers prefer steaks cooked to a medium or higher DOD (Cox et al, 1997;Schmidt et al, 2002;McKillip et al, 2017b) and therefore further examination of this theory could benefit the industry by identifying products that will meet consumer eating expectations based on their preferred degree of doneness. Thus, the objectives of this study were to evaluate the extent marbling and enhancement compensate for reduced beef palatability at elevated degrees of doneness and to determine the relationship of residual moisture and fat in cooked steaks to beef palatability, specifically beef juiciness.…”
Section: Introductionmentioning
confidence: 99%
“…Greater detail in regards to sample collection, fabrication, cookery, and sensory evaluation of samples used in this phase of the study is provided by McKillip et al (2017).…”
Section: Experimental Treatments and Sample Preparation -Phasementioning
confidence: 99%
“…Steaks representing a variety of USDA quality grades and enhancement levels were cooked to 3 degrees of doneness and evaluated for PJP [data reported by McKillip et al (2017)]. These PJP values were used to sort the steaks into the various categories identified by Lucherk et al (2017).…”
Section: Accuracy Of Pjp For Sorting Steaks For Juicinessmentioning
confidence: 99%
See 2 more Smart Citations